LEGAL POLICY ON THE ECONOMIC RIGHTS OF SONGRITERS IN ROYALTY DISPUTES IN THE MUSIC INDUSTRY - Aprianto Ihwan; Erham; Ilham (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
These research examines the inconsistency between legal rules and their application in practice the management within the song royalties on Indonesia. The findings of this study indicate that, normatively, safeguarding of creators' economic rights has been regulated in Copyright Law Number 28 of 2014 and Government Regulation Number 56 of 2021 on the Management of Song and/or Music Royalties and Regulation about the Minister of Ministerial Regulation of Law and Human Rights Number 9 of 2022, through a royalty management mechanism by Collective rights management organizations and the national collective management authority. However, in practice, that implementation of these regulations has not been optimal due to a lack of transparency, weak supervision, and low compliance by music users in paying royalties. Therefore, greater oversight is needed, increase transparency,enforce the verdict more strictly so that ensuring economic rights for songwriters can be carried out effectively.